Caminhos da rede : a experiência de uma regional do SUS na organização da Rede De Atenção Psicossocial (RAPS) a quem faz uso de drogas - Cuel, Brena Talita (2016)
The current debate about the "drug problem" in society has been the subject of major political and social actions. Recently, both the Ministry of Health and the Government of the State of São Paulo have provided urgently measures to combat this problem. The Psychosocial Care Network (PSCN) has been deploying as a guideline of these actions, in order to propose a redevelop of the health care services for people with mental disorders and other, who are addicted to alcohol and other drugs, seeking an articulation among territorial services to provide an adequately response to the demands for each region. In this context, it is proposed to know how the implementation of the PSCN in a determined Regional Health of the State of São Paulo has occurred, specifically on the care of the drug users, from the view of the mental health service technician. The methodology of the field in the Social Occupational Therapy is grounded on the discussion of the social role of the technician with special attention to the health technician. The regional in discussion has 26 cities and 29 specialized care services in mental health. 135 questionnaires were applied to the service technicians, an interview was conducted with the regional manager of mental health, eight questionnaires were applied to the municipal managers of mental health and a conversation was held with the technical team of a specialized service, CAPS-ad (Center of Psychosocial Care – Alcohols and Drugs), which is from a city that take part in this Regional. This study has showed that the process of the PSCN implementation is vertical and hierarchical, which hampers an effective articulated network among the technicians, even as the discussion about the intersectoriality and networking. The mental health area displays a restricted speech to its services, acting in a sectored way, away from the concept of networking and intersectionality. As a result, this study also brings the role ambiguous that the technician has, sometimes reproducing a technical and with it keeping the social order; sometimes illustrating the central role in the care of that population. Thus it has reflected ways and possibilities to think of mode of management and technical team, through the improvement of the social networks and the care of the person, individual and collective.